Evaluation of performance, emission and combustion characteristics of a CI engine fueled with karanja biodiesel and diethyl ether blends. Issue 1 (2nd January 2018) - Das, D.; Kumar, Anoop; Yadav, A.
ABSTRACT: In this experimental study, karanja biodiesel was prepared by two step transesterification process using potassium hydroxide as catalyst. This extracted biodiesel was used to determine performance, emission and combustion characteristics of different karanja oil diesel blends with 10% diethyl ether (DEE) at different loading conditions in an unmodified single cylinder, four-stroke compression ignition (CI) engine at 1500 rpm. Performance parameters evaluated are brake specific fuel consumption (BSFC) and brake thermal efficiency (BTE) while the emission of carbon dioxide (CO2 ), hydrocarbon (HC) and nitrogen oxides (NOX ) were calculated at 20, 40, 60, 80% and full load conditions. Combustion characteristics evaluated were in-cylinder pressure and heat release rate at full load condition. The results of the investigation have been compared with that of diesel. BTE and BSFC of biodiesel blends were found to be greater than diesel. Reduction in NOX and CO2 was observed at full load condition while there was an increase in HC emission on intermittent basis. Peak in-cylinder pressure and heat release rate of B10DEE10 and B20DEE10 were found to be greater than that of diesel at full load condition.